EXPERIENCES OF E-COMMERCE ADOPTION AMONG INDONESIAN FAMILY-OWNED SMES: A PHENOMENOLOGICAL STUDY - Martin Zebua (STMIK Indonesia Banda Aceh, 2026)
Family-owned MSMEs account for 99% of all businesses in Indonesia, yet only 30% survive into the second generation. Meanwhile, the adoption of e-commerce has become a competitive necessity, but it often clashes with the family values that form the foundation of these businesses. This study aims to uncover the lived experiences of family-owned MSME entrepreneurs in adopting e-commerce amid the pressure to preserve socioemotional wealth (SEW). Using interpretive phenomenological analysis (IPA), this study examines a case of a manufacturing SME in Central Java with five key informants. The results identified three essential themes: the founder’s existential ambivalence, the second generation’s struggle with dual legitimacy, and the renegotiation of senior employees’ loyalty. The findings yield a “Digitalized Personalized Formalization” model, which demonstrates that digitalization does not replace family values but rather reinterprets them through digital practices. The theoretical contribution lies in the modification of the SEW concept for the context of Indonesian collectivism, while the practical implications emphasize the importance of co-digital leadership training and digitalization programs that are sensitive to family dynamics.